Analisis Kandungan Kadmium, Fosfor, C-Organik dan Tingkat Keasaman Tanah Sawah di Desa Woloau Kecamatan Maurole - Siprianus Dawe; Charly Mutiara; Yovita Yasintha Bolly (Agriculture - Jurnal Ilmu Pertanian, 2026)
This study aims to determine the comparison of Cadmium content in rice field soil with the critical limit of cadmium in Woloau Village as well as the status of Phosphorus, soil organic C and soil acidity levels. This study is a descriptive study. The study was conducted in Woloau Village, Maurole District. The sample determination used the purposive sampling method and the method of taking it used disturbed soil samples. The variables observed were soil cadmium, Phosphorus (available P and total P), organic C and soil acidity levels. The results of the analysis of cadmium in the soil were seen by comparing the level of contamination with the critical limit of cadmium in the soil. Meanwhile, the content of Phosphorus, organic C and pH were compared with the soil chemical criteria from the Bogor Soil Research Center (1995). The Cadmium content in rice field soil in Woloau Village was 0.004 – 0.008. This content is still below the critical limit for the presence of cadmium in the soil. The total P content of 161.99 - 208.39 and available P of 95.01 - 101.9 in the paddy soil in Woloau Village are in the very high criteria, the soil pH content of 5 - 7 is classified as acidic to neutral, the organic C of paddy soil is 3.32 - 3.94 is included in the high criteria.